L'arte rupestre dell'età dei metalli nella penisola Italiana : localizzazione dei siti in rapporto al territorio, simbologie e possibilità interpretative - Grifoni Cremonesi, Renata,; Tosatti, Anna Maria, (Access archaeology., 2017)
This work presents the proceedings of the conference 'L'arte rupestre dell'età dei metalli nella penisola Italiana: localizzazione dei siti in rapporto al territorio, simbologie e possibilità interpretative' that took place in Pisa at the Cantiere delle Navi di Pisa under the aegis of the Soprintendenza Archeologica della Toscana and of the University of Pisa on 15th June 2015. The addressed issues were related to the Post-Pleistocene rock art along the Apennine ridge; in recent years more and more evidence has been identified, which is different from the magnificent evidence found in the Alps such as, for example, the well-known Monte Bego and Val Camonica.